2013
DOI: 10.1111/pcn.12105
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a Brief Self‐rated Scale of Health Condition with Acute Schizophrenia

Abstract: Aim:The aim of this study was to develop a new Brief Scale of Self-rated Health Condition with Acute Schizophrenia (BsHAS) and to examine its reliability, validity and correlation to psychiatric symptoms. Methods:We examined the reliability and validity of the BsHAS consisting of four items (physical health condition, mood, interpersonal fatigue and interest) for 199 inpatients with acute schizophrenia and compared the patients' subjective health conditions as assessed by the BsHAS with their objective psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, it may also reflect fundamental differences between the objective narrative clinicians have, and the subjective narratives that patients have about psychiatric symptoms. Indeed, although some data suggests that severely ill patients are unable to accurately report negative symptoms (Hamera et al, 1996; Selten et al, 2000), more recent studies have suggested that self-report measures may be both valid and useful in this patient population (Dollfus et al, 2016), especially in the assessment of treatment outcome and overall QoL (Fleischhacker et al, 2005; Lindstrom et al, 2001; Ohata et al, 2014). Thus, the present findings may add to a growing literature emphasizing the utility of self-reported symptoms in assessing patient-centered outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may also reflect fundamental differences between the objective narrative clinicians have, and the subjective narratives that patients have about psychiatric symptoms. Indeed, although some data suggests that severely ill patients are unable to accurately report negative symptoms (Hamera et al, 1996; Selten et al, 2000), more recent studies have suggested that self-report measures may be both valid and useful in this patient population (Dollfus et al, 2016), especially in the assessment of treatment outcome and overall QoL (Fleischhacker et al, 2005; Lindstrom et al, 2001; Ohata et al, 2014). Thus, the present findings may add to a growing literature emphasizing the utility of self-reported symptoms in assessing patient-centered outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8 CHU de Caen, Service de Psychiatrie, 14000 Caen, France. 9 Normandie Univ, UNICAEN, ISTS, GIP Cyceron, 14000 Caen, France.…”
Section: Fundingmentioning
confidence: 99%
“…Several tools were designed primarily to measure symptoms in patients with schizophrenia, most of which relied on hetero-assessments, of which the Positive and Negative Syndrome Scale (PANSS) that measures both negative and positive symptoms of patients. However, recent studies highlighted the importance of subjective assessment by schizophrenic patients [9], since it allows them to assess their overall functioning, and requires their participation in analyzing their symptoms. This can be considered as a basis for cognitive/social therapy of patients with schizophrenia [6], especially in the early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…These instruments evaluate the severity of negative symptoms based on the evaluation of the observer, but not on the patient's self-evaluation [7]. In fact, researchers believe that self-reporting complements objective evaluations of negative symptoms in schizophrenia, since patients are able to accurately express negative symptoms [7][8][9][10]. Moreover, patients' selfevaluation is important because it allows them to evaluate their overall performance and participate in the process of examining and analyzing their symptoms, which in turn encourages them to participate more in the treatment process [11].…”
Section: Introductionmentioning
confidence: 99%